2021
DOI: 10.1016/j.ccell.2021.08.006
|View full text |Cite
|
Sign up to set email alerts
|

Microbiome and cancer

Abstract: The human microbiome constitutes a complex multikingdom community that symbiotically interacts with the host across multiple body sites. Host-microbiome interactions impact multiple physiological processes and a variety of multifactorial disease conditions. In the past decade, microbiome communities have been suggested to influence the development, progression, metastasis formation, and treatment response of multiple cancer types. While causal evidence of microbial impacts on cancer biology is only beginning t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
181
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 326 publications
(227 citation statements)
references
References 301 publications
(331 reference statements)
0
181
0
1
Order By: Relevance
“…For example, Helicobacter pylori can bind to gastric epithelial cells through the adhesin HopQ and carcinoembryonic antigen-related cell adhesion molecules (CEACAM) and the virulence factor CagA is directly injected into epithelial cells through type 4 secretion system (T4SS). CagA could ultimately activate the Wnt/β-catenin pathway, leading to cell turnover and apoptosis ( 51 ). Pathogenic Escherichia coli has a complete set of virulence factors and toxins related to pathogenicity, including secretory genetic poison colibactin.…”
Section: Potential Pathogenic Mechanisms Of Microbiota In Pcmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, Helicobacter pylori can bind to gastric epithelial cells through the adhesin HopQ and carcinoembryonic antigen-related cell adhesion molecules (CEACAM) and the virulence factor CagA is directly injected into epithelial cells through type 4 secretion system (T4SS). CagA could ultimately activate the Wnt/β-catenin pathway, leading to cell turnover and apoptosis ( 51 ). Pathogenic Escherichia coli has a complete set of virulence factors and toxins related to pathogenicity, including secretory genetic poison colibactin.…”
Section: Potential Pathogenic Mechanisms Of Microbiota In Pcmentioning
confidence: 99%
“…Pathogenic Escherichia coli has a complete set of virulence factors and toxins related to pathogenicity, including secretory genetic poison colibactin. Once in the host cell, colibactin induces cross-links between DNA strands and double-strand DNA breaks ( 51 ). Pancreatic tissue could counter this malignant effect induced by the microbiota through an inflammatory response.…”
Section: Potential Pathogenic Mechanisms Of Microbiota In Pcmentioning
confidence: 99%
See 1 more Smart Citation
“…However, this methodology has limitations in analytical output and data interpretation, and exhibits poor reproducibility due to chimera generation and variation in the regions of 16S rRNA amplified gene and reference databases [ 69 ]. Therefore, a full RNA sequencing using methods like shotgun metagenome sequencing could allow improved characterization of the gut microbiome at the species and strain level compared to 16S rRNA gene sequencing method [ 70 ].…”
Section: Expert Opinionmentioning
confidence: 99%
“…Probiotics could regulate gut microbiota structure and composition, thus modulating occurrence and development of colon cancer 35,36 . The present studies suggested that the structure and abundance of gut microbiota were correlated with the development of colon cancer via administration for living or inactivated probiotics.…”
Section: In This Studymentioning
confidence: 99%